Macrocyclic‐Amphiphile‐Based Self‐Assembled Nanoparticles for Ratiometric Delivery of Therapeutic Combinations to Tumors. Issue 12 (18th February 2021) - Zhang, Zhanzhan; Yue, Yu‐Xin; Xu, Lina; Wang, Ying; Geng, Wen‐Chao; Li, Juan‐Juan; Kong, Xiang‐lei; Zhao, Xinzhi; Zheng, Yadan; Zhao, Yu; Shi, Linqi; Guo, Dong‐Sheng; et al.
Abstract: Combination chemotherapy refers to the use of multiple drugs to treat cancer. In this therapy, the optimal ratio of the drugs is essential to achieve drug synergism and the desired therapeutic effects. However, most delivery strategies are unable to precisely control the ratio of the drugs during the drug loading and delivery processes, resulting in inefficient synergy and unpredictable efficacy. Herein, a macrocyclic‐amphiphile‐based self‐assembled nanoparticle (MASN) that achieves precise loading and ratiometric delivery of therapeutic combinations is presented. By integrating multiple macrocyclic cavities within a single nanoparticle, the MASN can load multiple drug molecules via the host–guest interaction, and the ratio of the drugs loaded can be predicted with their initial concentrations and characteristic binding affinity. Moreover, MASNs are readily degraded under a hypoxic microenvironment, allowing spontaneous release of the drugs upon reaching tumor tissues. With precise drug loading and controlled release mechanisms, MASNs achieve ratiometric delivery of multiple commercial drugs to tumors, thereby achieving optimal anti‐tumor effects. Since the optimal drug ratio of a therapeutic combination can be quickly determined in vitro, MASNs can translate this optimal ratio to the therapeutic benefits in vivo, providing a potential platform for the rapid development of effective combination cancer therapies involving multiple drugs. Abstract : A macrocyclic‐amphiphile‐based self‐assembled nanoparticle (MASN) with the capability of precise loading and ratiometric delivery of different drugs is developed for effective combination chemotherapy. The MASN can quickly convert the optimal drug ratio of a therapeutic combination identified in vitro into therapeutic benefits in vivo, providing a potential platform for the rapid development of effective combinations of cancer therapies.